Reflexões sobre a abordagem da geografia nos cursos de graduação em turismo do Estado do RS, Brasil - Farias, Dione Rossi (2006)
The education is a preparation for the individual exercise his citizenship and qualify himself for work. It is mainly developed through the teaching, therefore, the superior educational institutions create the curriculum of each course, specifying the units and fields of study in order to be ministered. In this sense, the graduation courses in Tourism contemplate their curricular organization with studies related to basic, specific and practical-theoretical contents where Geography inserts itself in the basic formation axis while it is the science that studies the individuals and nature. From one selection of contents the disciplines of Geography correspond to a set of acquirements .Thus, this research pointed out the specificity of the Geography of Tourism, that is, it tried to specify the thematics expressed by theoretical concepts which sustain the current Geography teaching in the Superior Courses of Tourism in the state of Rio Grande do Sul, Brazil. For this, the work characterized the disciplines offered, besides identifying the theoretical focuses and the approach. It evaluates if this approach is compatible with the generalist proposal of formation of the Tourism Bachelor. The methodological resource used was the content analysis, under the thematic analysis modality. The research has an exploratory character and it utilized from the qualitative approach. The results were analysed and discussed through fourteen categories and respective units of meaning. It was evidenced that in the courses of Tourism in Rio Grande do Sul, Geography isn t only treated as an object for spatial localization, but it is mainly as a social process, reflex of the articulation of the interchanging relations between society and nature that produce the tourism and its developments. The approaches expressed by Thematical Categories are elements that constitute the geographical space, both the social point of viewand the natural. And, under the point of view of the predominancy of a General Geography, with social approach, one can infer that the generalist formation proposed by the Bachelor in Tourism according to the Curricular Directrices of the year 2003 is contemplated only by some courses which offer varying contents. It was concluded that there isn t a minimal reference content in Geography for the superior courses in Tourism of Rio Grande do Sul